Effect of sustainable poultry interventions on household food security and resilience in game management areas of Zambia's Luangwa Valley: a before-and-after study. (April 2017) - Dumas, S E; Lungu, L; Mulambya, N; Daka, W; Lewis, D; Travis, A
Abstract: Background: Zambia's Luangwa Valley epitomises the linked environmental, agricultural, and human health problems around protected wildlife areas in developing countries. Smallholder crop yields are usually poor, and farmers turn to the unsustainable harvesting of natural resources, including hunting, fishing, and deforestation for charcoal production to supplement household income and food supply. Chronic poverty and food insecurity are pervasive and long-term household and environmental resilience are uncertain. Village poultry can ameliorate these problems, through the provision of animal-source food and income and an alternative to consumption of natural resources. However, the returns on traditional backyard poultry ownership are reduced by high flock losses and poor flock genetics. We, therefore, designed and implemented two poultry interventions and measured their effect on productivity, profitability, and consumption of animal-source food. Methods: We implemented two programmes in the Luangwa Valley, Zambia. First, we undertook a community vaccination programme for Newcastle disease virus (NDV) in village chickens in Mambwe and Lundazi districts and gave flock owners instruction in improved management practices through workshops. We recorded changes in flock size over 4 years, using surveys administered every 4 months, and we used other primary and secondary data sources to assess changes in poultry-related income and chicken and egg consumption. For the second programme, we facilitated construction of semi-intensive egg production facilities in 24 communities. Layer-hen facilities each held 40 hens and were owned and operated by a group of 4–5 people. We recorded data on egg productivity (the number of eggs produced on a day divided by the number of hens in the flock on that day), poultry-related income, and egg consumption for 1 year using facility records, a semiannual survey, and qualitative interviews. Findings: In areas covered by the NDV vaccine programme, mean household flock size increased from 10·9 birds in July, 2007, to 25·7 birds in November, 2011 (p<0·0001). Mean annual income from poultry increased 138%, from US 16·89 to US 40·25, annually. Chicken and egg consumption was unchanged over the study period, reflecting farmers' preference to sell birds. Where new semi-intensive egg production facilities were introduced, mean egg productivity was 62·5% during the first 9 months between September, 2015, and May, 2016, and mean group net income was US30·28 per month. Some groups used this income to invest in other businesses, together or individually, while others used it during the so-called hungry season to buy maize for their own households. Although most eggs were sold, weekly egg consumption increased 118% in producer households (from 3·3 to 7·2 eggs per week), including 167% in women (from 0·9 to 2·4 eggs per week) and 263% in young children ages 6 to 36 months (from 0·8 to 2·9 eggs per week). Interpretation: NDV vaccination and improved management sustainably increased flock sizes and improved household income but had no direct effect on household consumption of animal-source food. By contrast, semi-intensive egg production businesses provided both consistent income and significant increases in consumption of animal-source food, not only promoting food security and resilience but also providing a potentially important alternative to bushmeat in villages surrounding ecologically-important protected areas. Funding: Atkinson Center for a Sustainable Future (AJT) and the National Institutes of Health (T32 OD011000, SED).